Preferencias Psicoterapéuticas: Versión argentina de las escalas PEX-1 y C-NIP-v1.1 - Santangelo, Pablo Rafael (2022)
We sought to adapt to the Argentine context two scales that assess psychotherapeutic preferences: The Cooper-Norcross Preferences Inventory (C-NIP-v1.1) and the Questionnaire of Preferences and Experiences of Psychotherapy for the Patient (PEX-1). We administered both scales in a sample of N=600 people (non-probabilistic). We performed internal consistency, dimensional, and item level analyzes. The internal consistency coefficients were adequate for the total scale and, in general, for each dimension. The confirmatory factor analysis evidenced an adequate fit to the original structures. The performance of the items for the scale and its dimensions was acceptable with few exceptions. The psychometric properties of the C-NIP-v1.1 and the PEX-1 are suitable for their application in our context.